Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Kompetensi Digital Guru TK - Andi Nur Maharani Islami; Rika Kurnia R; Fadhilah Afifah; Ramlah Yusran; Andi Makkasau (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity aims to enhance the digital competence of 20 kindergarten teachers in Bajeng District, Gowa Regency, in developing interactive learning media using the Canva application. The issues faced by the partners included low teacher digital literacy regarding the design of technology-based learning media and minimal utilization of online graphic design applications in early childhood education. The activity employed a participatory